How the COVID-19 Pandemic Impacted on Integrated Care Pathways for Lung Cancer: The Parallel Experience of a COVID-Spared and a COVID-Dedicated Center - Pasello, Giulia; Menis, Jessica; Pilotto, Sara; Frega, Stefano; Belluomini, Lorenzo; Pezzuto, Federica; Caliò, Anna; Sepulcri, Matteo; Cernusco, Nunzia Luna Valentina; Schiavon, Marco; Infante, Maurizio Valentino; Damin, Marco; et al. (Frontiers in Oncology, 2021)
Introduction COVID-19 pandemic has represented a historic challenge to healthcare systems, particularly for cancer patients. So far, very limited data have been presented on the integrated care pathways (ICP) impact. Methods We reviewed the ICPs of lung cancer patients who accessed the Veneto Institute of Oncology (IOV)/University Hospital of Padua (Centre 1) and University Hospital of Verona (Centre 2) before and after COVID-19 pandemic, through sixteen indicators chosen by multidisciplinary team (MDT) members. Results Two window periods (March and April 2019 and 2020) were chosen for comparison. Endoscopic diagnostic procedures and major resections for early-stage NSCLC patients increased at Centre 1, where a priority pathway for cancer patients with dedicated personnel was established, while a slight decrease was observed at Centre 2, which became part of the COVID unit. Personnel shortage and different processing methods of tumor samples determined a slight longer time for diagnostic pathway completion, at both Centres. Personnel protection strategies led to a MDT reshape on a web-basis and to a significant selection of cases to be discussed in both Centres. The optimization of patients access to healthcare units reduced first outpatient oncological visits, patients enrolment in clinical trials, and end-of-life cancer systemic treatments; finally, higher proportion of hypofractionation as radiotherapy approach for early and locally advanced stage NSCLC was shown. Conclusions: Based on the experience the two Centres went through, we identified the key steps in ICP impacted by a pandemic such COVID-19 so to proactively put in place robust service provision in thoracic oncology.